Pediatric Fractures - van Bergen, Christiaan J. A. (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint contains original research and review chapters concerning the latest advancements in various topics related to pediatric fractures. Topics include fractures of the face, clavicle, shoulder, elbow, forearm, wrist, pelvis, femur, and tibia; special considerations focus on osteogenesis imperfecta patients; and consideration is also given to general pediatric fracture topics, such as the influence of the COVID-19 pandemic, mortality after pediatric trauma, the effects of NSAID and electronic cigarette use, and chapters on epidemiology and physical activity.